Enhancing Public Services through Strategic Digitalization of Population Documents in Bandar Lampung City - Komsiyah Komsiyah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Population documents such as Identity Cards (KTP), Family Cards (KK), and Birth Certificates are basic rights of citizens and essential instruments for development planning, social protection, and public services. However, the effectiveness of population administration services still faces obstacles such as limited infrastructure, low adoption of digital services, and gaps in community digital literacy. This study aims to analyze the problems of population document services, formulate alternative solutions, and recommend strategic policies for digitalization. Using a qualitative policy research approach with a descriptive-analytical design, this study involved stakeholders from the Population and Civil Registration Office (Disdukcapil), government apparatus, and community representatives. Data were collected through document review, surveys, and in-depth interviews, analyzed using the Ultrasound (Urgency–Seriousness–Growth) method and the Bardach “Eightfold Path” framework to evaluate policy effectiveness, efficiency, and long-term implications. The findings show that dependence on manual services remains dominant due to weak infrastructure, limited digital capacity of the apparatus, and low community digital literacy. The policy evaluation identified three main alternatives: modernization of manual services, optimization of digitalization, and hybrid strategies. Strengthening digitalization supported by infrastructure improvement, capacity building, digital literacy enhancement, and multi-stakeholder collaboration was found to be the most feasible strategy. This study contributes by adapting the Avoid–Shift–Improve (ASI) framework into local digital governance analysis, providing a replicable model for other municipalities.